Revolutionizing Management: The Role of AI and Technology in Modern Leadership Practices - Uwase Shakilla; Edy Purwo Saputro (Walidem Institute and Publishing, 2025)
Objective: The incorporation of artificial intelligence (AI) and technological tools into managerial processes marks a significant evolution in modern leadership practices, driven by the need to address complex organizational challenges and capitalize on technological advancements. This study aims to investigate the impact of AI and technology on leadership practices, focusing on their implications for efficiency, adaptability, and employee engagement. Theoretical framework: The research is grounded in a theoretical framework that combines technological innovation with contemporary leadership models, emphasizing the role of AI-powered tools and project management software in enhancing managerial workflows. Literature Review: A literature review provides insights into previous studies that highlight the transformative potential of these technologies while addressing associated challenges, such as ethical concerns and employee resistance. Methods: Employing a qualitative methodology, this study analyzes case studies and relevant literature to explore how organizations integrate AI and technological tools to achieve competitive advantages. Results: The findings reveal that AI-driven insights significantly improve predictive analytics, enabling leaders to make strategic decisions, while project management software optimizes task allocation and communication, fostering team collaboration. However, challenges such as resistance to adoption and the need for employee training are identified as critical barriers to effective implementation. Implications: The study's implications are twofold: first, it offers a practical framework for leaders aiming to integrate AI and technology into their management practices, emphasizing strategies to enhance efficiency, decision-making, and teamwork; second, it highlights the importance of addressing ethical considerations and ensuring employee readiness through comprehensive training programs. Novelty: This research contributes novelty by providing a holistic perspective on the integration of AI and technology in leadership, bridging the gap between technological innovation and human-centric management approaches. By adopting the proposed framework, leaders can navigate potential challenges and leverage technological tools to transform their leadership practices, ensuring organizational adaptability and sustained success in a rapidly evolving landscape.